Design of concrete structures - Darwin, David; Nilson, Arthur H. (McGraw-Hill Education, 2016)
Ccompletely revised using the newly released 2014 American Concrete Institute (ACI) Building Code, this edition aims to establish a firm understanding of the behavior of structural concrete, and then to develop proficiency in the methods used in design practice